Nutritional composition and heavy metal content of farmed and wild seaweed (Gracilaria changii) - Mohd Nawi, Mohd Naeem (2015)
Gracilaria changii is edible seaweed that is cultivated commercially or found in its natural habitat. However, there is limited information regarding its nutritional composition and heavy metal content. In addition, no comparison between farmed and wild G. changii in terms of nutritional composition and heavy metal was found. Furthermore, there is insufficient previous information on mineral and heavy metal content of surface water for farmed (culture pond) and wild G. changii (mangrove forest). Proximate composition, mineral, water soluble vitamin, fat soluble vitamin, sugar, fatty acid, amino acid and heavy metal of farmed and wild G. changii were determined. Moisture content was found to be 74.47% in farmed G. changii and wild G. changii (71.12%). Protein, carbohydrate, total dietary fiber and ash were detected in farmed (17.11, 44.88, 32.43 and 32.60 g/ 100 g) and wild G. changii (12.30, 42.77, 40.53 and 41.27 g/ 100 g). Atomic absorption spectroscopy of the ashes showed that farmed and wild G. changii contained higher amount of potassium (2688.603-5504.927 mg/ 100 g) and sodium (887.168-2680.427 mg/ 100 g) than calcium, zinc, iron and copper. Positive correlation between G. changii and its surface water was found for zinc, copper and potassium (0.888, 0.972 and 1.000). For water soluble vitamins, vitamin C (0.076-0.337 mg/ 100 g), niacin (0.019-0.078 mg/ 100 g) and pyridoxine (0.004-0.006 mg/ 100 g) were detected. Palmitic acid (0.624-0.687 g/ 100 g) was the highest fatty acid detected and make up more than 80% of the total fatty acid detected. In terms of amino acids, valine (7.33-7.89%) and leucine (7.30-7.84%) were the highest essential amino acid found. Cadmium, lead, mercury and arsenic were found in farmed and wild G. changii although only mercury was within the permitted level according to Malaysian Food Regulations 1985. Negligible amount of cadmium, lead, mercury and arsenic were detected in culture pond and mangrove forest surface water. A positive correlation was found for cadmium and lead for wild G. changii and its surface waters. There is a positive correlation for arsenic content for farmed G. changii and its surface water. Seaweeds are used as ingredient to form gelling agent so the heavy metal content will be diluted during the manufacturing process. The heavy metal content does not reflect the safety consumption of G. changii. In summary, G. changii can be beneficial to the food industry as a supplement or halal ingredient due to its attractive nutritional properties such as dietary fiber, minerals and amino acids.